Method for Multiple Portal Vein Infusions in Mice: Quantitation of Adenovirus-Mediated Hepatic Gene Transfer. (February 1996) - Vrancken Peeters, Marie-Jeanne T.F.D.; Lieber, Andre; Perkins, James; Kay, Mark A.
For many preclinical studies, the mouse has been an invaluable model. For hepatic studies, including gene therapy, the use of the mouse has been limited because of the inability to obtain long-term portal vein access. In this study, we have developed a surgical cannula model that allows for repeat portal vein infusion in a noninvasive manner. We have used this model to establish that the tissue distribution of recombinant adenoviral vectors is similar after portal vein or peripheral vein infusion. The majority of the vector was present in the liver, ranging from 14 to 28 copies per hepatocyte. The second most prevalent tissues were the spleen and lung with 1 /10 less adenoviral DNA. The brain and ovaries had the least DNA, 1 /1000 less than the liver. Additional studies were performed to study the effects of secondary adenovirus infusion through the portal vein cannula. Permanent portal vein access in a mouse model will be invaluable for a large number of medical studies, including the development of new technologies for hepatic gene transfer.